A 640-Mb/s 2048-bit programmable LDPC decoder chip - Mansour, M.M.; Shanbhag, N.R. (IEEE journal of solid-state circuits, 2006)
A 14.3-mm/sup 2/ code-programmable and code-rate tunable decoder chip for 2048-bit low-density parity-check (LDPC) codes is presented. The chip implements the turbo-decoding message-passing (TDMP) algorithm for architecture-aware (AA-)LDPC codes which has a faster convergence rate and hence a throughput advantage over the standard decoding algorithm. It employs a reduced complexity message computation mechanism free of lookup tables, and features a programmable network for message interleaving based on the code structure. The chip decodes any mix of 2048-bit rate-1/2 (3,6)-regular AA-LDPC codes in standard mode by programming the network, and attains a throughput of 640 Mb/s at 125 MHz for 10 TDMP-decoding iterations. In augmented mode, the code rate can be tuned up to 14/16 in steps of 1/16 by augmenting the code. The chip is fabricated in 0.18-/spl mu/m six-metal-layer CMOS technology, operates at a peak clock frequency of 125 MHz at 1.8 V (nominal), and dissipates an average power of 787 mW.